Computer Mapping for the Equal Intensity Distribution of Heart Sounds and Murmurs on the Chest Surface - HAYASHI, RYUICHI (JAPANESE CIRCULATION JOURNAL, 1973)
The present study was undertaken to develope a practical method for displaying quantitatively the intensity distribution of heart sounds on the chest surface as the basic research for analyzing the mechanism of production and propagation of these sounds and murmurs. This report presents: (1) a digital computer method for drawing the equal intensity surface maps; (2) the apparatus for measuring the intensity of heart sounds and murmurs; (3) a clinincal application for normal subjects and patients with heart murmurs. Materials and methods The study was made in normal subjects and patients with typical heart murmurs, ranging in age from 20 to 30 years. The recording system consisted of micro-phone, preamplifier, high-pass filters, cathode-ray oscilloscope and photographic recorder. To explore the entire chest, a grid system was marked over the anterior thorax to record from 98 to 140 points. All measurements were made in only beats which occurred during resting expiration and the individual records include five or more cardiac cycles at a paper speed of 50 mm/sec.. A reference electrocardiogram (usually the standard limb lead 2) was simultaneously recorded. The gain setting of amplification was kept constant in all the phonocardiograms. All subjects were placed in the supine position and in a soundproof room. The oscillographic data were reviewed and the proper beats chosen for analysis. The maximum amplitudes of the first, the second heart sounds and murmurs were measured at the 98 or 140 points on the chest surface. In the second step, the values between the points at which the amplitudes were measured were estimated by linear interpolation. Finally, the equal intensity contour lines were automatically drawn on the chest maps with a drafting machine and displayed simultaneously on the cathode-ray oscilloscope. The programs developed herein consisted of about 420 FORTRAN steps. These procedures were executed by using a NEAC 22001500 computer and on-line TSS terminal.